Fiber-solid hybrid end-pumped Nd:YVO4 picosecond amplifier with high beam quality. (27th April 2021) - Liu, Minzhe; Liu, Menglin; Yan, Wei; Yang, Dewang; Wang, Lisha; Sun, Songsong; Jia, Zhongqing; Zhai, Ruizhan; Wang, Yong; Zhao, Kun
Abstract: In recent years, high-brightness picosecond lasers have been widely used in high-end precision processing, spectroscopy and high harmonic generation. To obtain higher power and excellent beam quality, it is an ideal solution to add a high-gain amplifier to the back end of the high-stability picosecond fiber or solid seed. In this article, a fiber-solid hybrid end-pumped Nd:YVO4 picosecond laser system with high beam quality is demonstrated. The influence of the self-developed picosecond fiber seed output characteristics on solid amplifiers has been studied in detail, including the energy, repetition rate and spectrum. After two-stage traveling wave amplifiers, the maximum 155 μ J single pulse energy is obtained with 20 kHz repetition rate, and the corresponding peak power reaches 14.9 MW with 10.4 ps pulse duration. Meanwhile, the beam quality factors under the maximum 18.4 W average power are measured to be M x 2 = 1.27 and M y 2 = 1.25, respectively.